Management of Communication Strategy by the Indonesian Television Journalists Association (IJTI) Tapal Kuda Jember in Enhancing Journalism Professionalism and Quality in the Digital Era - Azharghany, Rojabi; Munawwaroh, Umi Adibah (Journal of Educational Management Research, 2025)
Rapid technological developments require journalists not only to convey information accurately and quickly, but also to adapt to various emerging technologies in order to maintain professionalism and journalistic quality. This study aims to analyze the management of communication strategies implemented by a journalistic organization in addressing the challenges posed by digital transformation. Using a qualitative approach, this study explores various organizational efforts to improve member competence through journalism training programs, the utilization of digital media for education and information dissemination, and the strengthening of collaboration among journalists. Data were collected through in-depth interviews, direct observation, and documentation. The findings indicate that the organization has successfully managed digital technology to build an adaptive, participatory, and sustainable journalistic ecosystem. This strategic management approach not only enhances journalistic skills but also reinforces solidarity in facing global challenges in the media landscape. This study contributes to a deeper understanding of the urgency of innovation and digital transformation in the management of communication strategies within journalistic organizations.